Functional tag SNPs inside the DRD2 gene as a genetic risk factor for major depressive disorder in the Chinese Han population - He, Mei (Int J Clin Exp Pathol, 2019)
Background: The D2 dopamine receptor (DRD2) has been extensively investigated and has been associated with the occurrence of neuropsychiatric disorders. Polymorphisms in the DRD2 gene have also been determined as a possible predisposing component for major depressive disorders (MDD). The present study focused on evaluating the connection of polymorphisms inside the whole DRD2 gene in MDD patients as well as in non-MDD participants in a group selected from the Chinese Han population. Materials and methods: In total, 831 unrelated Chinese adults from the Han population were sampled, including 497 non-MDD participants and 334 MDD patients for this evaluation. After the haplotype bins were built, 14 tag single-nucleotide polymorphisms (tSNPs) and the two most investigated SNP were chosen for the whole DRD2 gene. An improved multiplex ligation detection reaction (iMLDR) technique was used to choose the genotypes. Following this, the allelic frequencies and clinical features were contrasted between the two independent Chinese Han populations. Transcriptional enhancer activities were measured to assess the functionality of the rs7131056 polymorphism. Results: Sixteen SNPs were identified, including the two most examined in the Chinese Han population, and all were recurrent SNPs. Of the 16 SNPs, two (rs4648317 and rs7131056) were significantly connected to MDD. Patients with MDD were more apt to carry the rs4648317G and rs7131056A allele in contrast to the non-MDD controls (P < 0.05). The genetic risk effect on MDD occurrence was associated with the haplotype GTGATCGCGCAGGC of fourteen tag SNPs (OR = 1.52, 95% CI: 1.06 to 2.18, P = 0.02). Moreover, the rs7131056 polymorphism contained intronic silencer activities. Conclusions: This case-control evaluation involving the Chinese Han population suggests that the rs4648317 and rs7131056 polymorphisms and the haplotype GTGATCGCGCAGGC inside the DRD2 gene could be possible markers to forecast vulnerability to MDD.